Diabetes during Pregnancy in Low- and Middle-Income Countries - Goldenberg, Robert L.; McClure, Elizabeth M.; Harrison, Margo S.; Miodovnik, Menachem (American Journal of Perinatology, 2016)
Objective Our objective was to review the literature in relationship to diabetes in pregnancy in low and middle income countries.Study Design We reviewed the English language literature related to diabetes and obesity during pregnancy in low and middle income countries published over the last 20 years.Results The global prevalence of diabetes mellitus is an estimated 8% with approximately 380 million adults with this condition worldwide. Ninety percent of diabetes in adults occurs in low- and middle-income countries (LMIC). However, diabetes is highly correlated with obesity and the highest diabetes rates occur in countries with the highest obesity rates. Hyperglycemia complicates 17% of pregnancies, including women with diagnosed and undiagnosed types 1 and 2 diabetes, and gestational diabetes mellitus (GDM). In many LMIC, as pregnancy becomes more common in wealthier, older, and more obese women, pregnancies complicated by pregestational diabetes and GDM will increase. Approximately half of women with hyperglycemia in pregnancy are undiagnosed. Even with diagnosis, because of the numerous tests and criteria for abnormal glucose levels used worldwide, the prevalence of hyperglycemia in pregnancy can only be approximated. Moving forward, a single set of tests and diagnostic criteria is recommended. Although the risk factors and pregnancy outcomes for pregestational diabetes and GDM are similar in LMIC to wealthier countries, they appear to occur more commonly, and with worse outcomes because of poor access to care. In the poorest areas, inadequate antenatal and general medical care increase the difficulty in managing diabetes and its complications for women and newborns.Conclusion As obesity among women increases, diabetes in pregnancy is becoming increasingly common in LMIC. Because of lack of resources and trained personnel, and other priorities related to reducing maternal, fetal, and neonatal mortality, diagnosing and providing care to women with diabetes in pregnancy is not high on the priority lists in many LMIC.
Keywords: diabetes; pregnancy; gestational diabetes; obesity; glucose testing